2013
DOI: 10.1891/0886-6708.vv-d-12-00068
|View full text |Cite
|
Sign up to set email alerts
|

Victims of Road Rage: A Qualitative Study of the Experiences of Motorists and Vulnerable Road Users

Abstract: Our analysis suggests that issues of victim vulnerability play a major role in determining the intensity, severity, and psychological consequences of road rage incidents. This seems particularly true for the most vulnerable of road users, such as pedestrians and cyclists.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 22 publications
0
6
0
1
Order By: Relevance
“…Moreover, cyclists are generally not accepted as equal road users (Granville et al, 2001). Cavacuiti et al (2013) reported that cyclists felt they were "second-class" citizens that did not deserve as much road space as cars.…”
Section: Cyclists As Minority Groupmentioning
confidence: 99%
“…Moreover, cyclists are generally not accepted as equal road users (Granville et al, 2001). Cavacuiti et al (2013) reported that cyclists felt they were "second-class" citizens that did not deserve as much road space as cars.…”
Section: Cyclists As Minority Groupmentioning
confidence: 99%
“…Moreover, anger leads to road aggression ( Demir et al, 2016 ), and power imbalance can take a key role in this relationship. Cavacuiti et al (2013) found that road users inside a vehicle felt more secure, with more power, and that power imbalance seemed to enhance how threatening potentially harmful actions or road aggression were perceived by the road user with less power.…”
Section: Introductionmentioning
confidence: 99%
“…Las personas más vulnerables a la agresividad o ira de los conductores en la carretera son los peatones y ciclistas, quienes se constituyen como víctimas al resultar lesionados tras un accidente. Ellos tienen más probabilidad de sufrir, a largo plazo, consecuencias relacionadas con su salud física y mental (Cavacuiti, et-al, 2013). Es preciso mencionar que, si bien la agresividad en la conducción es un concepto muy estudiado, no se ha llegado a un consenso entre investigadores (Dula, & Geller, 2003).…”
Section: Introductionunclassified